2006
DOI: 10.1002/ptr.1878
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant screening of medicinal herbal teas

Abstract: Herbal tea consumption is deeply and widely rooted amongst South-American populations. In view of the involvement of oxygen- and nitrogen-reactive species in the ethiogenesis of several diseases, the antioxidant properties of some of the herbal teas most commonly consumed in the southern regions was assessed in vitro. Around one-third of the 13 examined herbs, displayed a substantially higher ability to scavenge ABTS(+.) radicals (TEAC assay), and to quench the pro-oxidant species, hypochlorite (HClO) and pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 34 publications
1
30
0
3
Order By: Relevance
“…Many additives have long been used by the food industry to preserve their products from oxidation, usually synthetic antioxidants such as butylhydroxyanisole (BHA) and butylhydroxytoluene (BHT), with no clear effects after chronic consumption (Imaida et al 1983;Yanishlieva, 2001). Many plants are a source of compounds with antioxidant activity that might be used as natural preservatives (Dorman et al, 2003;Cai et al, 2004;Ansari et al, 2005;Chen et al, 2005;Hinneburg et al, 2006;Huang et al, 2006;Speisky et al, 2006;Wong & Kitts, 2006). In addition, antioxidants play a special role in human health care as in past years, prevention of cardiovascular diseases and cancer has been associated with the intake of fruits and vegetables rich in natural antioxidants (Patterson et al, 1990;Pietta, 2000;Sun, 1990Hertog et al, 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Many additives have long been used by the food industry to preserve their products from oxidation, usually synthetic antioxidants such as butylhydroxyanisole (BHA) and butylhydroxytoluene (BHT), with no clear effects after chronic consumption (Imaida et al 1983;Yanishlieva, 2001). Many plants are a source of compounds with antioxidant activity that might be used as natural preservatives (Dorman et al, 2003;Cai et al, 2004;Ansari et al, 2005;Chen et al, 2005;Hinneburg et al, 2006;Huang et al, 2006;Speisky et al, 2006;Wong & Kitts, 2006). In addition, antioxidants play a special role in human health care as in past years, prevention of cardiovascular diseases and cancer has been associated with the intake of fruits and vegetables rich in natural antioxidants (Patterson et al, 1990;Pietta, 2000;Sun, 1990Hertog et al, 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Teas and herbal infusions contribute to the major source of phenolic compounds in our diet [30,32]. More specifically, studies have suggested that regular consumption of some herbal teas may be potentially useful in providing protection against certain relevant oxidative species [31,34]. In view of the association between plant phenolics and anti-oxidant activity along with the recent thrust to market teas for their antioxidant properties, the content of total polyphenols, flavonoids and tannins were determined in search-me-heart infusions.…”
Section: Phenolic Constituents Of Search-me-heart Infusionsmentioning
confidence: 99%
“…In this sense, it is interesting to note that Rosa moschata infusions were among the most active in the removal of stable radicals (ABTS) 17,18 and reactive oxygen species (hypochlorite and peroxynitrite). 17 Furthermore, Rosa moschata is rich in ascorbic acid, 19 a compound that presents particularly high values of the ORAC-PGR index.…”
Section: Mosqueta > Mentha > Tilo > Llantén > Cedrón > Cocamentioning
confidence: 99%